Sustainable Production and Environmentally Responsible Consumption - Georgakellos, Dimitrios A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Achieving economic growth and sustainable development requires that we urgently reduce our ecological footprint by changing the way we produce and consume goods and resources. We consume more resources than the planet can generate, and growing rates of pollution and waste only worsen the problem. In this context, globally, a significant number of frameworks and programs on sustainable consumption and production have been introduced. Most of them concern the environmentally sound management of energy and raw materials and all wastes throughout their life cycle; the substantially reduce of waste generation through prevention, reduction, recycling and reuse; the adoption of sustainable practices and the integration of sustainability information into their reporting cycle; the promotion of procurement practices that are sustainable; the enhancement of scientific and technological capacity intending to more sustainable patterns of consumption and production etc. This reprint" Sustainable Production and Environmentally Responsible Consumption" takes a broad view of all these issues and aimed to inform about ways contributing to sustainable consumption and production by reducing our environmental impact, promoting the use of renewable sources of energy and encouraging responsible purchasing decisions.